Evaluation of Semantic Applications for Enterprises - Nekvasil, Marek (2011)
Broader and broader areas of application deployment are covered by semantic technologies recently and in the meantime their scope is increasing constantly. The possibilities of semantic applications are now so vast that they cannot be judged as a single market segment any more. The business skepticism that arises due to the uncertainty of investments in such technologies is only augmented by these differences and picking up on that this thesis concentrates on the aspects that can enable and evaluate not only the economic efficiency of engaging the semantic technologies in a business environment but also the effectiveness of doing so. This work concentrates on the ways of how to prove the differences amongst semantic applications, define their distinct segments based on use-case, and subsequently identify their Critical Success Factors and evaluate them against the real conditions of the applications' deployment with the participation of people involved in their development. Following the results of these interactions this thesis presents an innovative approach that enables to construct models for judging the maturity of enterprises for the deployment of the respective applications including the actual construction of these models for all the identified applications' use-cases segments. Moreover, in a later part of the work the evaluation using these models is demonstrated on AQUA application (outcome of a project the author did personally partake in) along with sketching additional specifics that may help the timely assessment of semantics in certain cases. The results presented in later chapters are supported by the underlying background researches in the fields of Semantic Technologies and IT assessment both of whose state-of-the-art methods are described here.